2018
DOI: 10.21608/ejnf.2018.75795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acetic Acid and Date Residues on Some Physiological Characteristics, Productive and Reproductive Parameters of Quail During Summer Season

Abstract: ne hundred and eight 8 wk-old Japanese quail were distributed randomly into six different dietary treatments in a 2 x 3 factorial with three replicates, each containing 6 birds (2 males and 4 females), assigning experimental unit to investigate the effect of vinegar (acetic acid) and date residues (date's by-product) on egg production, fertility and hatchability percentages, some physiological characteristics, blood parameters, hormones, antioxidant indices and immunity parameter. Average temperature ranged be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Saleh et al [49] declared that there was an antioxidative improvement in the lipids' peroxidation level, total phenolic amounts, and 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity with the increase in long-chain polyunsaturated fatty acids (n-3) in the thigh meat of chickens fed with 200 mg of α-tocopherol acetate (ester of acetic acid and α-tocopherol) per kg of diet. The same data were obtained by Fouad et al [8], who concluded that there was a protection effect from oxidative damage by adding 0.5 and 1 mL of vinegar/L of drinking water via the presence of escalating levels of antioxidative enzymes (GPX SOD) and glutathione in the serum of quails exposed to high-temperature stress during summer from 8 to 14 weeks. All these observations were confirmed in our research.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Saleh et al [49] declared that there was an antioxidative improvement in the lipids' peroxidation level, total phenolic amounts, and 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity with the increase in long-chain polyunsaturated fatty acids (n-3) in the thigh meat of chickens fed with 200 mg of α-tocopherol acetate (ester of acetic acid and α-tocopherol) per kg of diet. The same data were obtained by Fouad et al [8], who concluded that there was a protection effect from oxidative damage by adding 0.5 and 1 mL of vinegar/L of drinking water via the presence of escalating levels of antioxidative enzymes (GPX SOD) and glutathione in the serum of quails exposed to high-temperature stress during summer from 8 to 14 weeks. All these observations were confirmed in our research.…”
Section: Discussionsupporting
confidence: 81%
“…The improvement of productive characteristics of stressed birds in groups fed with a wet diet with vinegar might be related to the influence of acetic acid found in vinegar in lowering the pH, thus limiting pathogenic microorganism growth through shifting the composition of the microbiome [ 7 , 13 ] such as aerobic, anaerobic, and coliform bacteria [ 8 ] in avian gut. The reduction in fecal Escherichia coli and Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations